MENGEKSPLORASI DOKTRIN STANDING DI PERADILAN ADMINISTRASI INDONESIA: TAFSIR DAN HASIL - Efendi, A'an; Suwardi (Veritas et Justitia, 2025)
The authority to bring a claim before Indonesia’s administrative courts originates from the phrase “feeling that his interests have been harmed” in Article 53(1) of the State Administrative Court Act. Because this clause is open‑textured, it must be interpreted to define its exact reach. Using doctrinal legal analysis of court rulings and scholarly commentary on standing, this study concludes that two categories of plaintiffs can sue: (1) individuals or private legal entities that suffer direct losses from government acts or decisions, and (2) qualifying organizations. For an individual or private entity to obtain standing, it must demonstrate (i) a recognizable interest, (ii) a legal connection to the disputed act or decision, and (iii) harm to that interest caused by the government’s unlawful conduct. Organizational standing is available to bodies that satisfy statutory requirements to appear in court and that litigate not for their own interests but for the public purpose they were created to serve. Standing may also be granted when the harm is merely potential, allowing the administrative court to act preventively before actual damage occurs.